Preparing for a start into adulthood - young people in transition from education to the labor market - Lucyna Myszka-Strychalska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
Adulthood constitutes a time of not only intensive transitions taking place in almost all the aspects of the subject's functioning; it also involves a number of tasks that the individual is obliged to face in order to become an adult. One of them refers to the preparation of a young person for a career and participation in the labor market area. Looking at the actions of youth related to professional development turns out to be extremely interesting in cognitive terms because of the fact that in the near future they will become the creators of the labor market. This group is considered as the subject of social change, and on the basis of their behavior, various socio-cultural tendencies and phenomena are predicted. The issue of preparing young people to take on adulthood and to consider what factors condition it is therefore worth looking at. The results of our own research show a diverse picture of young people characterized by an uneven degree of preparation for 'taking off' into adulthood. The obtained empirical material indicates that the dominant tendency of respondents is to define themselves through the prism of individualistic properties that distinguish them from other people. When they reflect on themselves in the future, they define themselves through the perspective of the professional role they intend to play. The fact that more than a half of the respondents would like to pursue their chosen profession in the future testifies to the fact that the sphere of professional development is not indifferent to them.